Trophic eggs in the foam nests of Leptodactylus labyrinthicus (Anura, Leptodactylidae): An experimental approach - Prado, Cynthia P. A. [UNESP]; Toledo, Luís Felipe [UNESP]; Zina, Juliana [UNESP]; Haddad, Célio F. B. [UNESP] (My University, 2005)
The South American pepper frog, Leptodactylus labyrinthicus, is a large species that lays eggs in foam nests in holes dug out of the banks of different bodies of water. Recently, it was reported that only 6-10% of eggs are fertilized in foam nests of L. labyrinthicus and the remaining unfertilized eggs are consumed by the tadpoles inside the nest. Here we tested experimentally the influence of the ingestion of trophic eggs on the survivorship and growth of L. labyrinthicus tadpoles. Tadpoles fed on trophic eggs and subsequently fed on dry fish food grew larger than those fed only on dry fish food, and this suggests that the ingestion of trophic eggs is an adaptation to improve tadpole growth. The ingestion of trophic eggs also seems to be important for the maintenance of tadpoles in environments with unpredictable rainfall, as they were able to survive for about 70 days feeding only on these trophic eggs and one tadpole managed to complete metamorphosis feeding on trophic eggs only. Details of the spawning behaviour observed in the field, occurrence of multiple mating, and predation on eggs by terrestrial invertebrates and vertebrates are also reported.
Keywords: Egg predation; Frog; Multiple mating; Reproduction; Spawning behaviour; Anura; Invertebrata; Leptodactylidae; Leptodactylus labyrinthicus; Schinus molle; Vertebrata